Preparation method of low-expansion high-hardness ultrathin electronic glass
By adjusting the composition and process flow of raw materials in the glass, low-expansion, high-hardness ultra-thin electronic glass is prepared, which solves the problems of hardness and stability limitations in the existing technology, and achieves higher bending strength and transparency, which is suitable for a wider range of electronic equipment applications.
Patent Information
- Application Number
- CN202411813125.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-02-28
AI Technical Summary
The existing high-hardness ultra-thin electronic glass has limitations in improving hardness and stability, and it is difficult to meet a wider range of application scenarios.
By adjusting the composition and process flow of raw materials in the glass, including controlling the heating rate and temperature in the smelting furnace, using float molding and edge pulling machine to thinnify, combining annealing treatment and surface heat treatment, low-expanding and high-hardness ultra-thin electronic glass is prepared.
It realizes the low expansion, high hardness and high transparency of ultra-thin electronic glass, enhances its bending strength and scratch resistance, and is suitable for the cover protective layer of electronic equipment.
Smart Images

Figure CN119528418A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ultra-thin electronic glass, and in particular to a method for preparing ultra-thin electronic glass with low expansion and high hardness. Background Art
[0002] With the rapid development of new display technologies, low expansion and high hardness electronic glass has been favored by scholars at home and abroad. Low expansion can improve the stability and life of ultra-thin electronic glass products, and high hardness can improve the scratch resistance of glass, which also provides the possibility of improving more application scenarios of electronic glass products. Low expansion can be achieved mainly by increasing the boron content in the glass. Too high a content can easily lead to melting difficulties, so it is necessary to find a boron content balance suitable for low expansion ultra-thin electronic glass products. High hardness glass is mainly achieved by adjusting the glass network structure and microcrystallization treatment of the glass surface.
[0003] Existing high-hardness ultra-thin electronic glass usually places the glass in a high concentration of potassium nitrate for ion exchange, and improves the strength and hardness of the glass through chemical tempering. Ion exchange refers to the exchange of sodium ions and potassium ions in ultra-thin electronic glass. Since the radius of potassium ions is larger than that of sodium ions and a one-to-one exchange can be performed, the ions on the surface of the ultra-thin electronic glass can be squeezed against each other after ion exchange, thereby improving the surface hardness and strength of the glass. However, the scope of improving the hardness of glass by chemical tempering is limited. Ultra-thin electronic glass containing a crystalline phase obtained by heat treatment of the glass surface can significantly improve the hardness and strength of the glass.
[0004] Therefore, how to further improve the low expansion and high hardness performance of ultra-thin electronic glass has become a technical problem that needs to be solved urgently in the industry. Summary of the invention
[0005] In order to overcome the shortcomings of the background technology, the present invention provides a method for preparing ultra-thin electronic glass with low expansion and high hardness. The electronic glass prepared by the present invention is completely suitable for the cover protective layer of electronic equipment.
[0006] In order to achieve the above-mentioned purpose of the invention, the present invention adopts the following technical solution: A method for preparing low-expansion and high-hardness ultra-thin electronic glass, the method specifically comprising the following steps: The first step is to mix an appropriate amount of raw materials and put them into a melting furnace. The temperature of the melting furnace is controlled at 1620-1700°C to melt and obtain a uniform and stable glass liquid; The second step is to form the glass liquid obtained in the first step by float method, and set an edge drawing machine to thin it to obtain a base glass sheet with a thickness of 0.1 to 1.1 mm; Step 3: annealing the substrate glass sheet obtained in step 2 in an annealing furnace for 0.5 to 1 hour, and cooling the glass sheet to room temperature as the furnace cools; Step 4: Cut the base glass sheet obtained in the third step to obtain glass sheets of the required size, use alcohol and pure water to ultrasonically clean the glass sheets in turn, dry them in an oven at 105° C., then grind the dried glass sheets on a grinder using vacuum adsorption, measure the thickness of the ground glass sheets using a spiral micrometer, and make the average thickness reach 0.13 mm, wash and dry them again, polish the glass sheets on a polisher using vacuum adsorption, and then use a spiral micrometer to measure the thickness of the polished glass sheets, and make the average thickness of the glass sheets reach 0.12 mm, wash and dry the glass sheets again to obtain a transparent base glass sheet; Step 5: Soften the substrate glass sheet obtained in step 4, and put the softened substrate glass sheet into the annealing furnace again. The annealing time is 0.5 to 1 hour. After cooling down to room temperature in the furnace, the required qualified electronic glass is obtained.
[0007] In the method for preparing the low expansion and high hardness ultra-thin electronic glass, the raw materials in the first step include the following components by mass percentage: Na2O 8.12~18.25%; CaO 5.12~9.46%; SiO2 61.23~72.81%; Al2O312.15~25.69%; MgO 1.95~5.02%; K2O 0~1.35%; TiO2 0~5.14%; ZrO20~1.86%; B2O3 0~13.87%.
[0008] In the method for preparing the low-expansion and high-hardness ultra-thin electronic glass, in the first step, when the melting furnace melts the raw materials, the temperature is increased to a first set temperature at a first heating rate and then kept at a first set time, then the temperature is increased to a second set temperature at a second heating rate and then kept at a second set time, and then the temperature is increased to a third set temperature at a third heating rate and then kept at a third set time.
[0009] The method for preparing the low-expansion and high-hardness ultra-thin electronic glass is as follows: the first heating rate is 12-15°C / min, the first set temperature is 1620-1700°C, and the first set time is 200-300min; the second heating rate is 12-25°C / min, the second set temperature is 1050-1100°C, and the second set time is 120-250min; the third heating rate is 5-20°C / min, the third set temperature is 700-750°C, and the third set time is 100-500min.
[0010] In the method for preparing the low expansion and high hardness ultra-thin electronic glass, the annealing temperature of the annealing furnace in the third step is 700-750°C.
[0011] In the method for preparing the low expansion and high hardness ultra-thin electronic glass, the annealing temperature of the annealing furnace in the fifth step is 750-800°C.
[0012] By adopting the above technical solution, the present invention has the following advantages: In the present invention, Na2O and K2O are alkali metal oxides, which can reduce the melting temperature of glass and improve the formability. CaO and MgO can adjust the glass forming performance, play an alkali-reducing effect, and improve the stability of ultra-thin electronic glass. SiO2 is a network former in the structure of ultra-thin electronic glass. It forms an irregular continuous network with the structure of silicon oxygen tetrahedron [SiO4] to constitute the glass skeleton. Al2O3 is an intermediate oxide. When there are insufficient oxygen atoms in the glass, the coordination state of aluminum is aluminum oxygen octahedron [AlO6], which is in the network gap; when there are excess oxygen atoms in the glass, the coordination state of aluminum is aluminum oxygen tetrahedron [AlO4], which enters the ultra-thin electronic glass structure, plays a role in filling the network, increases the stability of ultra-thin electronic glass, and increases the strength of ultra-thin electronic glass. TiO2 and ZrO2 can adjust the density of glass, and B2O3 can adjust the thermal expansion coefficient of ultra-thin electronic glass. The ultra-thin electronic glass composed of the above components has good large-size performance, high strength, and high visible light transmittance. The glass prepared by the present invention has high bending strength, transparency and hardness. The surface is ground and polished and then heat treated to prevent the extension of cracks and increase the bending strength, transparency, hardness and the like of the glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is a microscopic magnified picture of the glass sheet in the embodiment of the present invention. DETAILED DESCRIPTION
[0014] The present invention can be explained in more detail by the following examples, but the present invention is not limited to the following examples; The object of the present invention is to provide a low-expansion, high-hardness ultra-thin electronic glass and a preparation method thereof, firstly preparing a high-quality, high-boron content batch material, then adjusting the content of aluminum oxide, magnesium oxide, calcium oxide, and sodium oxide, adjusting the glass network structure, preparing the electronic glass after molding and annealing, then performing surface heat treatment on the substrate glass to obtain a crystalline phase layer, and applying the crystalline phase layer to a cover protective layer of an electronic device.
[0015] In a specific implementation of the present invention, a method for preparing low-expansion and high-hardness ultra-thin electronic glass is provided, and the method specifically comprises the following steps: The first step is to mix an appropriate amount of raw materials and put them into a melting furnace. The temperature of the melting furnace is controlled at 1620-1700°C to melt and obtain a uniform and stable glass liquid; During implementation, the raw materials include the following components by mass percentage: Na2O 8.12~18.25%; CaO 5.12~9.46%; SiO261.23~72.81%; Al2O312.15~25.69%; MgO 1.95~5.02%; K2O 0~1.35%; TiO2 0~5.14%; ZrO20~1.86%; B2O3 0~13.87%; The present invention sets the above component contents so that the prepared glass has a lower expansion coefficient and higher hardness. The surface is ground and polished and then heat treated to prevent the extension of cracks and increase the hardness, transparency and bending strength of the glass.
[0016] Furthermore, when melting the raw materials, the smelting furnace heats the temperature to the first set temperature at a first heating rate and then keeps it for a first set time, then heats the temperature to the second set temperature at a second heating rate and then keeps it for a second set time, and then heats the temperature to the third set temperature at a third heating rate and then keeps it for a third set time. In specific practice, the first heating rate is 12-15°C / min, the first set temperature is 1620-1700°C, and the first set time is 200-300min, the second heating rate is 12-25°C / min, the second set temperature is 1050-1100°C, and the second set time is 120-250min, the third heating rate is 5-20°C / min, the third set temperature is 700-750°C, and the third set time is 100-500min.
[0017] The second step is to form the glass liquid obtained in the first step by float method, and set an edge drawing machine to thin it to obtain a base glass sheet with a thickness of 0.1 to 1.1 mm; Step 3: annealing the substrate glass sheet obtained in step 2 in an annealing furnace at a temperature of 700-750° C. for 0.5-1 h, and cooling the glass sheet to room temperature; Step 4: Cut the base glass sheet obtained in the third step to obtain glass sheets of the required size, use alcohol and pure water to ultrasonically clean the glass sheets in turn, dry them in an oven at 105° C., then grind the dried glass sheets on a grinder using vacuum adsorption, measure the thickness of the ground glass sheets using a spiral micrometer, and make the average thickness reach 0.13 mm, wash and dry them again, polish the glass sheets on a polisher using vacuum adsorption, and then use a spiral micrometer to measure the thickness of the polished glass sheets, and make the average thickness of the glass sheets reach 0.12 mm, wash and dry the glass sheets again to obtain a transparent base glass sheet; The fifth step is to soften the substrate glass sheet obtained in the fourth step, and then put the softened substrate glass sheet into the annealing furnace again. The annealing temperature is 750-800°C, and the annealing time is 0.5-1h. After cooling to room temperature in the furnace, the required qualified electronic glass is obtained.
[0018] In the specific implementation of the present invention, the thermal expansion coefficient of the substrate glass is 3.23*10 -6 / K, the three-point bending strength at room temperature can reach 120MPa, the transmittance in the visible light range is greater than 91%, and the electronic glass Vickers hardness value is 560~660kgf / mm 2 , such as Figure 1 shown.
[0019] The glass prepared by the invention has high bending strength, transparency and hardness. The surface is ground and polished and then heat treated to prevent the extension of cracks and increase the bending strength, transparency and hardness of the glass.
[0020] The glass composition selected by the present invention has a three-point bending strength of 120MPa at room temperature, a transmittance in the visible light range of more than 91%, a size of 2210*1240, and a density of less than 2.55g / cm 3 , such as Figure 1 shown.
[0021] When the present invention is implemented, high-quality batch materials are first prepared, and then the contents of aluminum oxide, magnesium oxide, calcium oxide, and sodium oxide are adjusted, and the glass network structure is adjusted. After molding and annealing, high-transmittance matrix glass is prepared and applied to the display layer of electronic equipment.
[0022] In the specific practice of the present invention, the best preparation method is as follows: The first step is to calculate the weight of the required raw materials according to the mass percentage and weigh them accurately, then heat the weighed raw materials to 1620-1700°C at a rate of 10°C / min and keep them warm for 100 minutes; Step 2: Cool the glass liquid to 1100℃, pour it onto the surface of the tin liquid, and stretch it into thin shape; Step 3: Place the glass sheet obtained in step 2 into an annealing furnace heated to 700-750° C. and cool it down to room temperature. Step 4: Cut the glass sheet obtained in the third step to obtain a 0.2 mm thick thin glass sheet, use alcohol and pure water to ultrasonically clean the 0.2 mm glass sheet in turn, dry it in an oven at 105° C., then grind it on a grinder using vacuum adsorption, measure its thickness with a spiral micrometer, and make its average thickness 0.13 mm, clean and dry it, polish it on a polishing machine using vacuum adsorption, measure its thickness with a spiral micrometer, and make its average thickness 0.12 mm, and clean and dry it to obtain a transparent substrate glass sheet; Step 5: According to the expansion softening point and glass transition temperature of the low expansion and high hardness electronic glass, set a suitable softening process, put the low expansion and high hardness electronic glass sheet into an annealing furnace, perform heat treatment according to the process, and obtain the low expansion and high hardness electronic glass.
[0023] The density of the low expansion and high hardness electronic glass prepared by the present invention is measured by a density meter and is 2.42 g / cm 3 The transmittance of the substrate glass under visible light wavelength was measured by a haze meter, and the average transmittance of the substrate glass under visible light wavelength was 91%, and the thermal expansion coefficient of the substrate glass was 3.23*10 -6 / K, the three-point bending strength at room temperature can reach 120MPa, and the Vickers hardness of electronic glass is 560~660kgf / mm 2 .
[0024] Parts of the present invention not described in detail are prior art.
[0025] The embodiments selected herein for the purpose of disclosing the invention are currently considered to be suitable, but it should be understood that the invention is intended to include all changes and modifications of the embodiments that fall within the scope of the concept and invention.
Claims
1. A method for preparing low expansion and high hardness ultra-thin electronic glass, characterized by: The method specifically comprises the following steps: The first step is to mix an appropriate amount of raw materials and put them into a melting furnace. The temperature of the melting furnace is controlled at 1620-1700°C to melt and obtain a uniform and stable glass liquid; The second step is to form the glass liquid obtained in the first step by float method, and set an edge drawing machine to thin it to obtain a base glass sheet with a thickness of 0.1 to 1.1 mm; Step 3: annealing the substrate glass sheet obtained in step 2 in an annealing furnace for 0.5 to 1 hour, and cooling the glass sheet to room temperature as the furnace cools; Step 4: Cut the base glass sheet obtained in the third step to obtain glass sheets of the required size, use alcohol and pure water to ultrasonically clean the glass sheets in turn, dry them in an oven at 105° C., then grind the dried glass sheets on a grinder using vacuum adsorption, measure the thickness of the ground glass sheets using a spiral micrometer, and make the average thickness reach 0.13 mm, wash and dry them again, polish the glass sheets on a polisher using vacuum adsorption, and then use a spiral micrometer to measure the thickness of the polished glass sheets, and make the average thickness of the glass sheets reach 0.12 mm, wash and dry the glass sheets again to obtain a transparent base glass sheet; Step 5: Soften the substrate glass sheet obtained in step 4, and put the softened substrate glass sheet into the annealing furnace again. The annealing time is 0.5 to 1 hour. After cooling down to room temperature in the furnace, the required qualified electronic glass is obtained.
2. The method for preparing the low expansion and high hardness ultra-thin electronic glass according to claim 1, characterized in that: The raw materials in the first step include the following components by mass percentage: Na2O 8.12~18.25%; CaO 5.12~9.46%; SiO2 61.23~72.81%; Al2O312.15~25.69%; MgO 1.95~5.02%; K2O 0~1.35%; TiO2 0~5.14%; ZrO20~1.86%; B2O3 0~13.87%.
3. The method for preparing the low expansion and high hardness ultra-thin electronic glass according to claim 1, characterized in that: In the first step, when the smelting furnace melts the raw materials, the temperature is increased to the first set temperature at a first heating rate and then kept at the first set time, then the temperature is increased to the second set temperature at a second heating rate and then kept at the second set time, and then the temperature is increased to the third set temperature at a third heating rate and then kept at the third set time.
4. The method for preparing the low expansion and high hardness ultra-thin electronic glass according to claim 3, characterized in that: The first heating rate is 12-15°C / min, the first set temperature is 1620-1700°C, and the first set time is 200-300min. The second heating rate is 12-25°C / min, the second set temperature is 1050-1100°C, and the second set time is 120-250min. The third heating rate is 5-20°C / min, the third set temperature is 700-750°C, and the third set time is 100-500 min.
5. The method for preparing the low expansion and high hardness ultra-thin electronic glass according to claim 1, characterized in that: The annealing temperature of the annealing furnace in the third step is 700-750°C.
6. The method for preparing the low expansion and high hardness ultra-thin electronic glass according to claim 1, characterized in that: The annealing temperature of the annealing furnace in the fifth step is 750-800°C.